2006
DOI: 10.1093/jn/136.4.998
|View full text |Cite
|
Sign up to set email alerts
|

Excessive Weight Gain during Pregnancy Increases Carcinogen-Induced Mammary Tumorigenesis in Sprague-Dawley and Lean and Obese Zucker Rats

Abstract: Excessive weight gain during pregnancy increases breast cancer risk in women. To determine whether this may be caused by increased pregnancy leptin levels, leptin receptor (Ob-Rb) mutant (fa/fa) and wild-type (FA/FA) female Zucker rats and Sprague-Dawley rats were fed during pregnancy an obesity-inducing high-fat diet (OID) that increased pregnancy weight gain, or a control diet. Because mutant Zucker rats do not readily become pregnant, their pregnancy was mimicked by exposing the rats to subcutaneous silasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 46 publications
2
22
0
1
Order By: Relevance
“…This appears to be downstream of MAPK, and not PI3K/AKT signaling, because AKT phosphorylation was inconsistently induced in repetitions of this experiment ( Figure 5). DMBA has been shown to both induce and decrease MAPK levels and signaling in animal carcinogenesis models (22)(23)(24)(25)(26)(27). Variables shown to be associated with these disparate results are mutations that arise during tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…This appears to be downstream of MAPK, and not PI3K/AKT signaling, because AKT phosphorylation was inconsistently induced in repetitions of this experiment ( Figure 5). DMBA has been shown to both induce and decrease MAPK levels and signaling in animal carcinogenesis models (22)(23)(24)(25)(26)(27). Variables shown to be associated with these disparate results are mutations that arise during tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, lean Zucker (+/fa or +/+) rats show almost normal metabolic functions, and have been used as controls in various types of physiochemical and pathological experiments (Bray, 1977). The Zucker rat has been recognized as a superior model to investigate effects of obesity on chronic disease development, including cancer (Bray, 1977;de Assis et al, 2006;Hakkak et al, 2007), but its utility for investigations of mammary carcinogenesis is limited due to scant epithelial development in mature mammary glands of obese as compared with lean counterparts (Hu et al, 2002). Since it was reported that young heterozygous lean Zucker (+/fa) rats demonstrate a number of differences from wild type lean Zucker (+/+) rats, e.g., higher body weights, fat cell size, inguinal fat pad weights, pad-to-body weight ratios, serum cholesterol, adipose tissue lipoprotein lipase and glycerol-3-phosphate dehydrogenase, hepatic and adipose tissue 6-phosphogluconate dehydrogenase activities and serum leptin levels (1.6 and 0.9 ng/ml in +/fa and +/+, respectively, ) Heo et al, 2002;Phillips and Cleary, 1994;Truett et al, 1995;Zhang et al, 1997), we here investigated whether they might provide the basis for a leptin-related mammary carcinogenesis model.…”
Section: Introductionmentioning
confidence: 99%
“…The latter express defective leptin receptors (Ob-R), which cause them to become morbidly obese, particularly when fed high-fat diet [52] . In all three models, consumption of OID and excessive weight gain during pregnancy increased dams ' later mammary tumorigenesis [53] . However, neither E2 nor IGF-1 levels were associated with excessive weight gain during pregnancy, but leptin was.…”
Section: Exposures To Excess Estrogens or Leptinmentioning
confidence: 91%
“…However, as discussed below, there is some evidence that mothers with the highest range of estrogens during pregnancy are at elevated breast cancer risk [51,52] . Furthermore, elevated pregnancy leptin [53] , and perhaps IGF-1 levels, may increase mothers ' later breast cancer risk.…”
Section: Growth Factorsmentioning
confidence: 99%